Parental expectations and adolescents’ happiness: the role of self-efficacy and connectedness - Feng Zhang; Rui Yang (BMC Psychology)
Abstract Background A happy adolescent may live a healthy and successful life. This study focused on parental expectations in the Chinese cultural context and investigated whether and under what conditions adolescents’ perceived parental expectations are associated with their happiness, the affective component of subjective well-being. Sample and methods This cross-sectional study included a sample of 1510 Chinese adolescents; the average age of the adolescents was 12.39 years, and 55.40% were boys. A questionnaire including the perceived parental expectations scale, self-efficacy scale, connectedness subscale and one item that measured happiness was administered to the adolescents. Results The results reveal that self-efficacy moderates the relationship between perceived parental expectations and happiness. For adolescents who exhibit higher levels of self-efficacy, perceived parental expectations are negatively correlated with happiness; in contrast, for adolescents who exhibit lower levels of self-efficacy, perceived parental expectations are not related to happiness. Moreover, the results reveal that connectedness moderates the relationship between perceived parental expectations and happiness. Among adolescents who exhibit higher levels of connectedness, a nonsignificant relationship is observed between perceived parental expectations and happiness; in contrast, among adolescents who exhibit lower levels of connectedness, perceived parental expectations are negatively related to happiness. Conclusions This study reveals that, under conditions featuring higher levels of self-efficacy or lower levels of connectedness, perceived parental expectations are not conducive to their happiness. These findings have important implications with regard to parenting practices.